Texting against abuse and violence - Bautista, Kimberly (Technical Centre for Agricultural and Rural Cooperation, 2012)
A text message-based helpline helps women in Guatemala to prevent and report physical and sexual abuse. Text messages are not only cheap but also much less intimidating for victims of violence in their delicate search for help